2007
DOI: 10.1088/0022-3727/40/4/045
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear optical properties of (Pb,La)(Zr,Ti)O3ferroelectric thin films grown by radio-frequency magnetron sputtering

Abstract: Linear and nonlinear optical properties of lanthanum-modified lead zirconate titanate (Pb0.92La0.08)(Zr0.65Ti0.35)O3 (PLZT 8/65/35) ferroelectric thin films are presented in this paper. The PLZT ferroelectric thin films were grown on quartz substrates by radio-frequency magnetron sputtering at 650 °C. Their crystalline structure and surface morphologies were examined by x-ray diffraction and atomic force microscopy, respectively. It was found that the PLZT thin films exhibit well-crystallized perovskite struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…The obtained nonlinear optical properties are comparable to other films deposited by using RF magnetron sputtering [10,54]. The larger values of n 2 , and b, were obtained for the film deposited in pure oxygen atmosphere and are 2.46 Â 10 À5 cm 2 /W and 5.02 cm/ W, respectively.…”
Section: Linear and Nonlinear Optical Propertiessupporting
confidence: 79%
“…The obtained nonlinear optical properties are comparable to other films deposited by using RF magnetron sputtering [10,54]. The larger values of n 2 , and b, were obtained for the film deposited in pure oxygen atmosphere and are 2.46 Â 10 À5 cm 2 /W and 5.02 cm/ W, respectively.…”
Section: Linear and Nonlinear Optical Propertiessupporting
confidence: 79%
“…The granular surface of films is typical of post-annealed films formed from amorphous film precursors. It was also observed in others materials [34] and is relatively independent of the buffer layer [35,36]. The root-mean-square (rms) roughness surface roughness is about 4.4 nm and 7.6 nm for PtS and BaM/PtS substrates.…”
Section: ) Results and Discussionsupporting
confidence: 61%
“…Oscillating transmittance spectra were observed for 200 nm and 400 nm films, suggesting that they have a flat surface and a uniform thickness. [37][38][39] It was also observed that the number of oscillations decreases with decrease of film thickness. Optical absorption edge was observed at wavelength $300-350 nm (see Fig.…”
Section: Optical Characterizationmentioning
confidence: 91%